Adoption Of Industrialised Building System (Ibs) In Building Projects Based On Disaster Risk Management Cycle - Pauzi, Nurshelawati Mohd (Universiti Sains Malaysia, 2022)
The Industrial Building System (IBS) was introduced in the construction industry early in the 1960s. It is a term used to describe a construction method that produced building components manufactured in a factory, transported and assembled into a structure using appropriate machinery and equipment without requiring a maximum number of workers on site. Generally, the project life cycle starts from the starting point of manufacture until the moment it is successfully delivered to the site. The phases or stages used in a construction project are initiating, planning, executing, monitoring and controlling as well as the closing stages. In this context, the use of the project life cycle is very appropriate to the real purpose because this research is used the disaster risk management cycle to find out whether adoption of Industrial Building System (IBS) can be adopted or not based on the disaster risk management cycle consisting of prevention, preparedness, response and recovery. In addition, the concept of construction using IBS is intended to show that it is a method that produces productivity and quality in the aspects of sustainability that contribute to the use of the construction industry. However, the acceptance of adoption of IBS in Malaysia has not been fully adopted due to the lack of in-depth knowledge related to IBS. So, it is hoped that this research can provide opinions to construction stakeholders to realize that adoption of IBS can provide various benefits and can be used as a future reference for comparative studies.